Electronic Circuits / Discrete and Integrated: Third Edition - Belove Charles; Schilling Donald L (Mcgraw Hill Book Company, 1989)
Preface, Diode-Circuit Analysis, Introduction to Transistor Circuits, The Field-Effect Transistor, Bias Stability, Audio Frequency Linear Power Amplifiers, Small-Signal Low-Frequency Analysis and Design, Multiple-Transistor Circuits, Applications of Operational Amplifiers, Frequency and Switching-Speed Limitations, Feedback and Frequency Compensation of Op-Amps and Oscillators, Logic Functions and Boolean Algebra, Logic Gates, Flip-Flops, Register and Counters and Arithmetic Circuits, Sample-Hold Circuits and Digital-to-Analog and Analog-to-Digital Converters and Timing Circuits, Circuit Fabrication and Its Effect on Performance and Density and Cost, Asic Design Methodologies and System Design Considerations, Comuter-Aided Design Software for VLSI Design, Appendices, Index.